FREQUENCY OF THYROID DYSFUNCTION AMONG ANTENATAL PATIENTS WITHOUT KNOWN THYROID DISEASE, PRESENTING AT FAROOQ HOSPITAL WESTWOOD, LAHORE (The Research of Medical Science Review, 2025)
INTRODUCTION: Thyroid disease is the second most common endocrine disorder after diabetes in pregnancy. Thyroid disease poses a substantial challenge to the physiology of pregnant women and has significant maternal and foetal implications. OBJECTIVE: To determine the frequency of thyroid dysfunction among antenatal patients presenting at Farooq Hospital Westwood, Lahore STUDY DESIGN: Descriptive, Cross-sectional study SETTING: Department of Obstetrics & Gynaecology, Farooq Hospital Westwood, Lahore. DURATION OF STUDY: Six months from the date of acceptance of synopsis. From 21-7-2022 to 18-1-2023.METHODOLOGY: After approval from the institutional ethical review committee, a total of 124 women presenting to the outpatient department, fulfilling the inclusion criteria were selected. A thorough general physical examination was done. Patients were subjected to systemic and obstetric examination. Along with routine blood investigations, specifically serum levels of free T3 and T4 as well as TSH levels were also determined. The presence or absence of thyroid dysfunction was noted. RESULTS: In this study, mean age was 27.63+3.88 years, 84(67.7%) were primiparous and 40(32.3%) were multiparous, and 19(15.3%) had thyroid illness, whereas 105(84.7%) did not, 5 (4%) had overt hypothyroidism, 9(7.3%) had subclinical hypothyroidism, 3(2.4%) had overt hypothyroidism, 2(1.6%) had preclinical hyperthyroidism, and 105(84.7%) had no thyroid illness. CONCLUSION: We concluded that the frequency of thyroid dysfunction is not very high but considerable among antenatal patients presenting at Farooq Hospital Westwood, Lahore.